The family Calyptraeidae in Peru (Gastropoda: Caenogastropoda) - Paredes, Carlos (2006)
In the present work the taxonomic of the family Calyptraeidae Lamarck, 1809 in the Peruvian coast are reviewed. The presence of 17 species of the 19 is confirmed reported by diverse authors. Crepidula arenata (Broderip, 1834) is synonymous of C. excavata (Broderip, 1834). Information on the distribution geographical and same relations ecological is presented.